Waist-to-height ratio associated cardiometabolic risk phenotype in children with overweight/obesity. - Ukegbu, Tochi E; Wylie-Rosett, Judith.; Groisman-Perelstein, Adriana E; Diamantis, Pamela M; Rieder, Jessica.; Ginsberg, Mindy.; Lichtenstein, Alice H; Matthan, Nirupa R; Shankar, Viswanathan. (Tufts University. Tisch Library., 2023)
Keywords: Cardiometabolic risk, Waist-to-height ratio, Insulin resistance, Liver enzymes, AST, ALT.; Springer Open.